Shikonin Inhibits Cancer Through P21 Upregulation and Apoptosis Induction - Wang, Fangfang; Mayca Pozo, Franklin; Tian, Danmei; Geng, Xinran; Yao, Xinsheng; Zhang, Youwei; Tang, Jinshan (Frontiers in Pharmacology, 2020)
Shikonin is a natural naphthoquinone compound and has demonstrated potent anti-cancer activities; however, the underlying molecular mechanisms remained elusive. Here we report that Shikonin inhibited the growth of a wide range of human cancer cell lines, illustrating a broad anticancer effect. Mechanistically, we show that Shikonin arrested the cell cycle at the G2/M phase, inhibited the ERK-dependent cell growth signal, and induced cell death in both P53 wild type and mutant cancer cells, which collectively contributed to the growth inhibitory effect of Shikonin. A pan-apoptosis inhibitor largely suppressed Shikonin-induced cell death, suggesting an important role of apoptosis in this process. Intriguingly, Shikonin also activated autophagy and inhibition of autophagy by depleting critical autophagic genes further increased Shikonin-induced cell death, indicating a protective role of autophagy. In uncovering the molecular mechanisms underlying these effects of Shikonin, we found that Shikonin induced a robust upregulation of P21 independent of the P53 status, upregulated autophagy genes, as well as inhibited expression of genes required for cell growth. Using mouse tumor models, we confirmed the strong anticancer effect of Shikonin in vivo. Together, our data reveal a broad range of pharmacological functions of Shikonin, involving simultaneous growth inhibition, cell cycle arrest, autophagy activation and apoptosis induction through regulating expression of critical genes involved in these pathways. Our study may facilitate the development of Shikonin in cancer therapy as a single agent or in combination with other anticancer therapies.